2022
DOI: 10.3390/cancers14215190
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Impact of Hypofractionated and Stereotactic Radiotherapy on Immune Cell Subpopulations in Cancer Patients

Abstract: We investigated how hypofractionated radiotherapy (HFRT) and stereotactic body radiotherapy (SBRT) may impact immune cells in different type of tumors. A systematic review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The PubMed, Embase and Cochrane databases were searched. Overall, 11 studies met the inclusion criteria and were eligible for the present analysis. Both HFRT and SBRT have different impact on lymphocyte subpopulations, confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Preliminary studies have demonstrated a significant modification of both the tumor immune environment and the peripheral immune cell landscape after hypofractionated and stereotactic regimens. 16 This is exemplified by a recent randomized phase 2 trial, where the combination of stereotactic ablative RT with immunotherapy showed a notable improvement in event-free survival in early-stage non-small-cell lung cancer. 17 Exploring the combination of hypofractionated or stereotactic ablative RT with immunotherapy holds promise, crucial for revealing RT's immunomodulatory impacts and enhancing our grasp of its therapeutic possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies have demonstrated a significant modification of both the tumor immune environment and the peripheral immune cell landscape after hypofractionated and stereotactic regimens. 16 This is exemplified by a recent randomized phase 2 trial, where the combination of stereotactic ablative RT with immunotherapy showed a notable improvement in event-free survival in early-stage non-small-cell lung cancer. 17 Exploring the combination of hypofractionated or stereotactic ablative RT with immunotherapy holds promise, crucial for revealing RT's immunomodulatory impacts and enhancing our grasp of its therapeutic possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that radiation-induced immune modulation is governed by various factors, such as dose, fractionation, sequencing with other therapies, and intrinsic radiosensitivity [30,31]. Hypofractionated high-dose regimens appear to elicit abscopal responses more readily than conventional fractionation [32]. This difference may be related to differences in lymphocyte apoptosis induction between regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer appointments and/or shorter treatment courses provide numerous opportunities for patients to decrease spending and time away from work [13]. Hypofractionated regimens are being increasingly used both for curative as well as palliative treatments in brain malignancies, head and neck cancers, thoracic cancers, colorectal cancers, pancreatic cancers, gynecological cancers, skin cancers, and palliation, among others [14]. We discuss a few recent examples of the cost-effectiveness of hypofractionated short-course radiation.…”
Section: Radiation Oncologymentioning
confidence: 99%